LAND COVER CHANGE IN PROTECTED FOREST, TANANTOVEA SUBDISTRICT DONGGALA REGENCY - Anwar; Rhamdhani Fitrah Baharuddin; Hasriani Muis; Arman Maiwa; Muhammad Adam Suni; Abdul Rahman (Jurnal Belantara, 2026)
Protected forests play a vital role in maintaining ecosystem balance, such as regulating water systems, controlling floods, and preserving soil fertility. However, pressure from population growth and community activities around forest areas particularly land clearing for plantations has led to significant changes in land cover. This research was conducted from May to November 2023 and aimed to calculate the land cover area for the years 2013 and 2023, as well as analyze land cover changes in the Protected Forest area of Tanantovea District, Donggala, over the ten-year period. Land cover identification and its changes were assessed using Landsat 8 satellite imagery, classified through a supervised classification method. Image data processing identified five types of land cover: primary dryland forest, secondary dryland forest, plantations, shrubs, and bare land. The results showed that the primary dryland forest experienced a decrease of 522.20 hectares, while other land cover classes increased in area. These changes were driven by the socio-economic conditions of surrounding communities, such as low-income levels, limited employment opportunities, and small land ownership. The classification accuracy reached 82%, indicating that the image interpretation was reasonably representative of actual field conditions. These findings highlight the importance of utilizing remote sensing technology to monitor land cover dynamics and support sustainable forest management decision-making.